Association Between Incorrect Posture and Adolescent Idiopathic Scoliosis Among Chinese Adolescents: Findings From a Large-Scale Population-Based Study - Yan, Bin; Lu, Xinhai; Qiu, Qihua; Nie, Guohui; Huang, Yeen (Frontiers in Pediatrics, 2020)
Objectives: Adolescent idiopathic scoliosis (AIS) affects between 1 and 4% of adolescents, and severe curvature may be related to their adverse long-term outcomes. However, whether the change in body appearance is related to AIS remains largely unclear. We aimed to explore the association between incorrect posture and AIS among Chinese adolescents. Methods: Data were collected from a population-based (595,057) school scoliosis screening program in China. A sample of 3,871 adolescents was classified as cases with a diagnosed radiological lateral Cobb angle ≥10°, and 3,987 control subjects with a Cobb angle <10° were randomly selected from the screening system. Adolescents were accessed with demographic information and incorrect posture measured by visual inspection of physical signs, Adam's forward bending test (FBT), and the angle of trunk rotation (ATR). Logistic regression (LR) models were used to examine the associations. Results: Multivariate LR showed that shoulder-height difference, scapula tilt, lumbar concave, and pelvic tilt were associated with AIS. Adolescents with angle of thoracic rotation ≥5° [adjusted odds ratio (AOR) = 5.33–14.67, P < 0.001], thoracolumbar rotation ≥5° (AOR = 4.61–5.79, P < 0.001), or lumbar rotation ≥5° (AOR = 7.49–7.85, P < 0.001) were at especially higher risk for AIS than those with ATR <5°. Conclusions: Incorrect posture may be the potential risk factor for developing AIS, and ATR ≥5° was an important indicator for predicting the occurrence of scoliosis. Early monitoring of incorrect posture for school adolescents should be considered as a routine intervention to effectively identify the progress of scoliosis.